Study of the extraction process of papain from latex of papaya (carica papaya l.) fruits cv. maradol (2011)
In this work, we studied the extraction process of papain, present in the latex of papaya fruit (Carica papaya L.) cv. Maradol.  The variables studied in the extraction of papain were: latex:alcohol ratio (1:2.1 and 1:3) and drying method (vacuum and refractance window).  Papain enzyme responses were obtained in terms of enzymatic activity and yield of the extraction process. The best result in terms of enzyme activity and yield was obtained by vacuum drying and a latex:alcohol ratio of 1:3. The enzyme obtained was characterized by physicochemical and microbiological properties and, enzymatic activity when compared with a commercial sample used as standard.